Exploring the Origin of Fake News. A Case Study on Persuasion, Distortion and Emotion in the News (2020)
This article analyzes the relationship between digital leisure time and social class. To do so, it synthesizes and interprets the results of a research that studied everyday life in a group of middle-class households in Cali (Colombia). The objective of the research was to understand the emergence of leisure experiences at home, and to characterize the way in which human and non-human agents connect to produce differentiated home cultures. With this purpose, and following a qualitative approach, 69 structured interviews, 26 non-structured comprehensive interviews, 10 ethnographic visits and 10 cartographies were carried out in different households. Two seemingly unrelated findings were identified in this research: On the one hand, there is an everyday experience of uncertainty, expressed in a positional inconsistency that characterizes the condition of middle class in the country; and on the other, digital leisure has a central position as part of the routines in the homes studied. This article intends to integrate these two concepts. It will be suggested that common practices in these households, such as frequent technology updates and high levels of digital leisure, can be understood as markers of social class and, as control mechanisms over the present, and as ways to compensate the uneasiness produced by an uncertain future, by increasing their conditions of abundance. It is expected to shed light over the tensions experienced by middle classes, and the compensatory practices that emerge to improve their wellbeing.